2012
DOI: 10.1038/modpathol.2011.156
|View full text |Cite
|
Sign up to set email alerts
|

Role of molecular studies in the diagnosis of lung adenocarcinoma

Abstract: Molecular alterations in adenocarcinoma of the lung have resulted in new therapeutic options for treatment of high-stage disease. Such changes are usually mutually exclusive and can be documented in small specimen samples. Most analyses are DNA-based, utilizing sequencing or fluorescence in situ hybridization to observe amplifications or translocations. Particular success in theranostics has focused on epidermal growth factor receptor (EGFR), anaplastic lymphoma kinase gene (ALK), and BRAF gene changes, each a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
2
12
1
Order By: Relevance
“…A total number of 60 patients out of the 860 NSCLC stage IV patients tested positive for ALK mutation, and thus in principle were eligible for Crizotinib therapy. This latter number corresponds to a percentage of 3.8% ALK-positive NSCLC in the entire cohort, thus being in a range comparable to other cohorts [ 26 ]. Out of the 60 patients who were, in principle, eligible for Crizotinib therapy, only 22 received Crizotinib therapy, whilst the remaining patients received alternative or palliative therapy.…”
Section: Resultssupporting
confidence: 60%
“…A total number of 60 patients out of the 860 NSCLC stage IV patients tested positive for ALK mutation, and thus in principle were eligible for Crizotinib therapy. This latter number corresponds to a percentage of 3.8% ALK-positive NSCLC in the entire cohort, thus being in a range comparable to other cohorts [ 26 ]. Out of the 60 patients who were, in principle, eligible for Crizotinib therapy, only 22 received Crizotinib therapy, whilst the remaining patients received alternative or palliative therapy.…”
Section: Resultssupporting
confidence: 60%
“…38 Whether previous studies 30,[39][40][41] have demonstrated that mucinous adenocarcinomas of the lung tend to be wild-type at EGFR mutational analysis, herein we observed that also the other variants of primary lung and metastatic mucin-producing adenocarcinomas do not harbor EGFR mutations. Several works have underlined the significant relationship between ALK rearrangement and signet ring cell pattern of lung adenocarcinomas, [42][43][44] …”
Section: Rossi G Et Alsupporting
confidence: 49%
“…Improper regulation of Sox genes have been demonstrated to be associated with cancerous development of various types of cancer [20], such as gastric cancer [41,42], brain tumors [43,44], ovarian cancer [45], adenocarcinoma [4649], hepatocarcinoma [50], breast cancer [5153], melanomas [54], prostate cancer [5558], colon carcinoma [59], and the lung cancer [18,36,6069]. The role of the Sox gene family in the cancerogenesis has been attributed to their properties involving in the regulation of cell differentiation, proliferation, and survival in multiple essential processes.…”
Section: Sox Genes and Lung Cancermentioning
confidence: 99%